Sensational : the hidden history of America's "girl stunt reporters" - Todd, Kim, 1970- (Harper, an imprint of HarperCollinsPublishers, 2021)
Presents a social history of women journalists of the Gilded Age who went undercover to champion women's rights and expose corruption and abuse in America.